Light alloys : metallurgy of the light metals - Polmear, I. J.; StJohn, David; Nie, Jian-Feng; Qian, Ma (Butterworth-Heinemann, 2017)
Light Alloys: From Traditional Alloys to Nanocrystals, Fifth Edition, covers the materials science, properties, manufacturing processes, and applications of key engineering metals in a single accessible volume. As use of these metals is now more widespread than ever, with routine use in motor vehicles and aircraft, this book includes materials characteristics and applications, heat treatment properties, fabrication, microstructure/property relationships, new applications, and processes. Provides a definitive, single volume overview on the light alloysPresents new material on the processing, characteristics, and applications of these essential metalsCovers the latest applications and processes in the auto and aero industries.